The Use of English Songs to Teach Listening Skill - Maria Ulfa (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
There are four English skills that determine the learner’s performance in English. One of the very important skills is listening. The successful learning not only depends on the learner but also to the teacher. Teaching listening is one of the important thing that English teacher must know how to teach it. Teaching listening is not easier because not all of learners like listening. The teacher must create the enjoyable atmosphere, fun and interesting situation as possible as teacher can. The enjoyable atmosphere will have good effects on the education, because if they dislike the subject it will drop their spirit as soon as possible. In other word, the teacher should make learning enjoyable because many students like listening song and learn well when they are enjoying themselves. Using song can be boastful to motivate the students in learning English as well to enhance their ability in listening skill.